Konsep Kurikulum Merdeka pada Pembelajaran Pendidikan Agama Islam di tingkat SMA - Nova Riska Nurafianti; Aisyah Hidayah; Miftahul barhoya; Fiqra Muhammad Nazib (Yayasan Al-Afif, 2024)
This research aims to find out the concept of an independent curriculum in PAI learning in several schools at the Senior High School level. This research method uses the literature review study method with the stages of determining the theme, collecting articles, reducing articles, compiling selected articles, discussing and making conclusions. The research used 15 articles from the selection of 30 articles obtained from various sources with publication years from 2019-2024. The focus of the study consists of 3 aspects, namely the concept, implementation and evaluation of the independent curriculum. The results showed that: 1) The concept of an independent curriculum is implemented in several schools, by designing a syllabus at the beginning of learning, 2) The implementation of an independent curriculum is by applying teaching modules, 3) The evaluation of the independent curriculum includes three aspects, namely: Diagnostic, Formative and Summative Assessments